Estudios de raquis de diferentes cultivos en la elaboración de humus de lombriz (Eisenia toetida) como alternativa para la alimentación y aprovechamiento de residuos vegetales en la zona de Quevedo. - Zambrano Loor, Edison Rafael (2015)
This research was conducted in the same area Quevedo held at the Experimental Farm "Dam" owned by the State Technical University of Quevedo (UTEQ), located at km. 6.1 / 2-San Carlos Quevedo, province of Los Rios Ecuador in the months of November 2014 to February 2015 via. The local climate is tropical, annual average temperature of 24.8 ° C, annual rainfall of 2252.5 mm, relative humidity of 84% and 894.0 hours heliophany annual average, studying plant residues such as: Spine Palm, Coconut and Bananas for making vermicompost as an alternative use of plant residues while eliminating potential insect hosts. Was raised as a general objective to evaluate the contributions of the spine in the quality of worm and as specific, evaluate the quality of compost with conducting chemical and biological analysis, and determine the organic matter in the treatments, determining the ratio carbon / nitrogen treatments and economic analysis of the cost of production of vermicompost............................